Loss of β2-integrin function results in metabolic reprogramming of dendritic cells, leading to increased dendritic cell functionality and anti-tumor responses - Heidi Harjunpää; Riku Somermäki; Guillem Saldo Rubio; Manlio Fusciello; Sara Feola; Imrul Faisal; Anni I Nieminen; Liang Wang; Marc Llort Asens; Hongxia Zhao; Ove Eriksson; Vincenzo Cerullo; et al. (OncoImmunology)
Dendritic cells (DCs) are the main antigen presenting cells of the immune system and are essential for anti-tumor responses. DC-based immunotherapies are used in cancer treatment, but their functionality is not optimized and their clinical efficacy is currently limited. Approaches to improve DC functionality in anti-tumor immunity are therefore required. We have previously shown that the loss of β2-integrin-mediated adhesion leads to epigenetic reprogramming of bone marrow-derived DCs (BM-DCs), resulting in an increased expression of costimulatory markers (CD86, CD80, and CD40), cytokines (IL-12) and the chemokine receptor CCR7. We now show that the loss of β2-integrin-mediated adhesion of BM-DCs also leads to a generally suppressed metabolic profile, with reduced metabolic rate, decreased ROS production, and lowered glucose uptake in cells. The mRNA levels of glycolytic enzymes and glucose transporters were reduced, indicating transcriptional regulation of the metabolic phenotype. Surprisingly, although signaling through a central regulator of immune cell metabolisms, the mechanistic target of rapamycin (mTOR), was increased in BM-DCs with dysfunctional integrins, rapamycin treatment revealed that mTOR signaling was not involved in suppressing DC metabolism. Instead, bioinformatics and functional analyses showed that the Ikaros transcription factor may be involved in regulating the metabolic profile of non-adhesive DCs. Inversely, we found that induction of metabolic stress through treatment of cells with low levels of an inhibitor of glycolysis, 2-deoxyglucose (2DG), led to increased BM-DC activation. Specifically, 2DG treatment led to increased levels of Il-12 and Ccr7 mRNA, increased production of IL-12, increased levels of cell surface CCR7 and increased in vitro migration and T cell activation potential. Furthermore, 2DG treatment led to increased histone methylation in cells (H3K4me3, H3K27me3), indicating metabolic reprogramming. Finally, metabolic stress induced by 2DG treatment led to improved BM-DC-mediated anti-tumor responses in vivo in a melanoma cancer model, B16-OVA. In conclusion, our results indicate a role for β2-integrin-mediated adhesion in regulating a novel type of metabolic reprogramming of DCs and DC-mediated anti-tumor responses, which may be targeted to enhance DC-mediated anti-tumor responses in cancer immunotherapy.